Effect of Compost Tea and Harvest Age on Productivity, Nutrient Content, and In vitro Digestibility Cichorium Intybus - Rezki Amalyadi; Nafiatul Umami; Nanung Agus Fitrianto; Chusnul Hanim; Bambang Suwignyo (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
The glass house experiment involving compost tea and harvest age was conducted to investigate the effect of giving compost tea (cricket and rabbit feces) and harvesting age on productivity, nutrient content, and in vitro digestibility value of Cichorium intybus. Compost tea (CT) is an aqueous extract from compost that can correct nutrient deficiencies during crop production and protect cultivation. The research treatment consisted of two factors, namely: the age of harvest and the dose of compost tea. The administration of compost tea consisted of three kinds of doses as follows: no compost tea (P0), 200 mL of compost tea (P1), and 400 mL of compost tea (P2). The experimental plants were harvested at different age, consisting of 25, 35 and 45 days after planting (DAP). The experimental design was Factorial Completely Randomized Design (CRD) with 6 treatments and 9 replications. The data were statictically analyzed using analisys of variance, and differences among value of each treatment were tested with the Duncan Multiple Range Test. The results indicated that compost tea dose and harvesting period treatment affected (P<0.05) leaf length, fresh leaf weight, crude protein content, dry matter digestibility (DMD), and organic matter digestibility (OMD). Meanwhile, it showed not significant effect (P>0.05) on the leaf width and root length. The results suggest that the fertilization treatment of 200 mL of compost tea and 25 DAP could increase productivity (leaf length and fresh leaf weight) of chicory, nutrient content (crude protein) of chicory, and in vitro digestibility (DMD and OMD).